Faktor-Faktor Yang Berhubungan Dengan Tindakan Penjamah Dalam Penanganan Makanan Pada Rumah Makan Di Kabupaten Banjar - Perdana Oktavianus Kurniawan; Darmiah Darmiah; Rahmawati Rahmawati (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2018)
The Factors Associated With Handler’s Action In Handling Food On Restaurants In Banjar District. In 2015 there are poisoning cases because of contaminated food by chemical, physical, and biological factors. The case occurred in Gambut Subdistrict, Kertak Hanyar, Simpang Empat and Martapura, cause South Kalimantan in the sixth province with the highest poisoning case in Indonesia. The poisoning cases of 66.7% is caused by microbial contamination on fast food from the handlers. This is because their action who are less concerned on food safety, especially they work at house. This study aimed to determine the factors associated with the handler’s action in handling food on restaurants in Banjar District. The study type was Observational Research with Cross sectional design. The method used interview and observation. The sample was determined by purposive sampling technique, which is obtained by research opinion, with the result obtain a sample amounted to 78 food handlers that work for 24 restaurants in Martapura, Banjar District. The results showed that there was significant relationship between: 1) the education and handler’s action (p